Artha Meaning : testimony and the theory of meaning in Indian philosophical analysis - Ganeri, Jonardon (New Delhi ; Oxford : Oxford University Press, 2006)
The author highlights the significant relationship between semantic power and epistemic power to understand the important philosophical category of meaning.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Meaning (Philosophy); Philosophy, Indic -- Language